Morbidity and mortality of infective endocarditis in a hospital system in New York City serving a diverse urban population. Issue 6 (20th May 2016) - Alkhawam, Hassan; Sogomonian, Robert; Zaiem, Feras; Vyas, Neil; El-Hunjul, Mohammed; Jolly, JoshPaul; Al-khazraji, Ahmed; Ashraf, Amar
Abstract : Infective endocarditis (IE) is a severe illness associated with significant morbidity and mortality. The primary purpose of this study was to evaluate morbidity and mortality of IE in a hospital serving the most diverse area in New York City. An analysis of 209 patients admitted to the hospital from 2000 to 2012 who were found to have IE based on modified Duke criteria. Among the 209 patients with IE, 188 (88.8%) had native heart valves and 21 (11.2%) had prosthetic valves. Of the patients with native heart valves, 3.7% had coronary artery bypass graft, 4.3% were active drug users, 6.3% had permanent pacemakers, 12.2% had a history of IE, 25.7% were diabetic, 17% had end-stage renal disease (ESRD), 9% had congestive heart failure, 8% had abnormal heart valves, and 13.8% had an unknown etiology. Mortality rates of the patients with prosthetic heart valves were 27.7% compared to 8.11% in patients with native heart valves (OR 3, p<0.0001). Since we identified diabetes mellitus and ESRD to be significant risk factors in our population, we isolated and compared characteristics of patients with and without IE. IE among patients with diabetes mellitus was 23% compared with 13.8% in the control group (p=0.016). Cases of IE in patients with ESRD were 15.3%, compared with 4% in the control group (p<0.0001). We identified an overall mortality rate of 20.1% in patients with IE, a readmission rate within 30 days of discharge of 21.5%, and an average age of 59 years. Among 209 patients, 107 were males and 102 females. The most common organisms identified were Staphylococcus aureus (43.7%), viridans streptococci (17%) followed by Enterococcus (14.7%). Despite appropriate treatment, high rates of morbidity and mortality remained, with a higher impact in patients greater than 50 years of age. Such discoveries raise the importance of controlling and monitoring risk factors for IE.